Salivary pH changes caused by cariogenic and non-cariogenic food intake in preschoolers from Huaura, Peru - César Félix Cayo-Rojas; Esthefany Cindy Gerónimo-Nieto; Ana Sixtina Aliaga-Mariñas (Editorial Ciencias Médicas, 2021)
Introduction: Salivary pH, an important factor in caries prevention, is under the direct influence of diet type. Objective: Evaluate salivary pH changes caused by cariogenic and non-cariogenic food intake in preschoolers from an educational institution in Huaura, Peru. Methods: An observational longitudinal comparative study was conducted of a sample of 30 preschoolers. After the children consumed cariogenic and non-cariogenic food, their salivary pH was evaluated at various times. Student's t-test and the Mann-Whitney U test were used to contrast results. Results: Salivary pH with a non-cariogenic diet at five minutes was 7.11 ± 0.19 and 7.09 ± 0.20; whereas at 40 minutes it was 7.46 ± 0.19 and 7.42 ± 0.22, in female and male participants, respectively. Salivary pH with a cariogenic diet in women was 6.56 ± 0.21 at five minutes and 7.15 ± 0.12 at 60 minutes, whereas values in men for the same time ranges were 6.47 ± 0.32 and 7.23 ± 0.22, respectively. Comparison between the cariogenic and non-cariogenic diet groups revealed very significant differences (p < 0.01). Conclusions: With a cariogenic diet, pH is reduced at five minutes maximum, and is restored as of 60 minutes. With a non-cariogenic diet, pH is reduced in the same time period, but is restored at 40 minutes. This process is similar in the two genders.